Penggunaan Media Audio-Visual Dalam Meningkatkan Hasil Belajar Siswa Kelas VII Pada Pembelajaran Fiqih: Studi Kasus Di Mts Salafiyah Syafi’iyah Seblak Jombang - Zidni Ilman Nafi’; Sholihul Anshori (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to analyze the effectiveness of using audio-visual media in improving student learning outcomes in Fiqh subjects for seventh-grade students at MTs Salafiyah Syafi’iyah Seblak Jombang. The research was motivated by low student engagement and comprehension due to the dominance of one-way lecture methods. A qualitative case study approach was used, involving Fiqh teachers, the school principal, and seventh-grade students as research subjects. Data were collected through participatory observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman model. The findings reveal that the use of audio-visual media significantly enhances learning quality across cognitive (material comprehension), affective (attitude toward learning), and psychomotor (worship practice skills) domains. Students became more active, enthusiastic, and found it easier to grasp procedural content. Additionally, the media strengthened the teacher’s role as a facilitator and fostered a more interactive and contextual learning environment. In conclusion, audio-visual media represent an effective and relevant instructional strategy for more applicable and transformative Islamic education.